Terrorism and Violent Extremism in North-Eastern Nigeria: Toward a Model of Radicalization of the Almajiri Cohort - Usman, Abbo; Mohd. Zain, Zawiyah; Ali, Salim Ibrahim (GoDaddy, LLC., 2017)
Despite the existence of a voluminous studies on Radicalization and violent Extremism the concept is still new within the Nigerian context, as there is absence of empirical model explaining the why and how of the African version of Radicalization, in spite of the increasing surge of insurgency and terrorist related activities in the continent. This therefore creates the need to study the factors that shape the development of homegrown extremist within the African context. More so, as all the existing models of Radicalization are context-specific and are not in a complete harmony with one another hence the simple question of how do some individual subscribes to violent extremism remains to a larger extent unanswered, due to lack of valuable framework upon which assumption shall be made on the basis of theoretical paradigm. This paper intends to contribute to the heated debate on the linkage of the Almajiri system and insurgency in the North-eastern Nigeria. It’s therefore explored the societal practices and individual factors responsible for revamping the support for terrorism among the Almajiri cohorts in northeastern Nigeria, specifically the roles of sociocultural factors in encouraging conviction and involvement, as well as the contribution of myriads of push and pull factors such as unfavorable sociopolitical condition, economic strain and grievances. The work adopts an ethnographic design in which data were collected through indepth-interview, focus group discussion and personal observation. The data were thus analyzed in light of theoretical paradigm and previous models in which factors such as bad governance, collective strain, target attribution, cultural resistance; social identity and social learning were identified and discussed